Componential Analysis of Ana/Mat'/Mother Words: Mother Prototype Extension - Bakenova, I.; Mazhitayeva, Sh.; Kenzhegaliyev, S.; Zhartybayev, A.; Balmagambetova, Zh.; Yesmatova, M. (Theory and Practice in Language Studies, 2023)
The research is aimed at identifying the specifics of ana (mother -Kazakh)/mat’ (mother-Russian)/mother semantic broadening in the Kazakh, Russian and English languages. The componential analysis method of lexicalized word definitions is used to do this. It has been revealed that they present a prototype of mother semantic markers, as well as “woman”, “giving birth”, “raising”, and “single-generation” distinguishers, which produce the intention meaning. It is important to emphasize that a “mother” prototype semantic broadening is associated with the changes in the world around us, the development of health reproduction technologies, as well as the change of social values. Implicational meanings arise due to variation of “giving birth”, “raising”, “having”, “kinship” intentional functional and relational semes, e.g. a surrogate mother, a birthmother, a genetic mother, etc. This leads to a mother’s ideal prototypical image “blurring” in the minds of native speakers.
Keywords: component analysis; mother prototype; intention; implication; distinguisher